The action of tubocurarine and atropine on the normal and denervated rat diaphragm - Beránek, R. (1967)
1. The potency with which tubocurarine chloride (TC) and atropine sulphate (AS) influence the amplitude of the end-plate potentials was measured in the rat diaphragm. This effect was compared with the action of these drugs on brief depolarizations evoked by iontophoretic application of ACh to end-plate-free spots of the chronically denervated fibre. 2. TC and AS act similarly on e.p.p.s, but the concentrations necessary to cause the same effect are 2000-times higher for AS. 3. The dose—response curves for both inhibitors are unchanged by prostigmine. 4. Ten to twenty-five days after denervation the ACh-potentials of the sensitized end-plate-free parts of the membrane are less responsive to curare than the normal e.p.p.s are. AS is as effective in blocking ACh potentials of denervated muscles as it is in blocking normal e.p.p.s. The curare/atropine coefficient (dose ratio for equal effect) is 0·0005 for e.p.p.s and 0·003 for ACh potentials of the denervated membrane. 5. Both blocking drugs reduce the amplitude of ACh-potentials evoked in the end-plate region of normally innervated rat diaphragm fibres as effectively as they reduce the amplitude of e.p.p.s. 6. Neither TC nor AS have a presynaptic action in concentrations markedly reducing the e.p.p. amplitude.